2017
DOI: 10.1080/00313831.2017.1324901
|View full text |Cite
|
Sign up to set email alerts
|

Parental Involvement in Math Homework: Links to Children’s Performance and Motivation

Abstract: The present study examined the longitudinal associations between children's perceptions of parental involvement in math homework (control and support) and their math performance and motivation (taskpersistent homework behavior and math self-concept). Children (n = 512) reported their perceptions concerning parental involvement in sixthgrade math homework. In grades 3 and 6, children completed math tests, evaluated own math self-concept, and their mothers (n = 420) evaluated task persistence during homework. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
126
6
34

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(206 citation statements)
references
References 72 publications
13
126
6
34
Order By: Relevance
“…The effects of both these parental involvement types in homework are inconclusive in the literature. For instance, while some studies found a positive relation of parental autonomy support and academic performance (Doctoroff & Arnold, 2017;Dumont et al, 2012;Moroni et al, 2015;Núñez et al, 2015), others report contradictory results (e.g., Karbach et al, 2013;Silinskas & Kikas, 2019;Valle et al, 2016). Some scholars (Dinkelmann & Buff, 2016;Fan & Williams, 2010;Gonida & Cortina, 2014;Hoover-Dempsey et al, 2001;Karbach et al, 2013;Luo et al, 2016; argue these contradictions are because parental involvement in homework has a stronger association with children's psychological resources than with academic achievement.…”
Section: Types Of Parental Involvement With Homeworkmentioning
confidence: 99%
See 4 more Smart Citations
“…The effects of both these parental involvement types in homework are inconclusive in the literature. For instance, while some studies found a positive relation of parental autonomy support and academic performance (Doctoroff & Arnold, 2017;Dumont et al, 2012;Moroni et al, 2015;Núñez et al, 2015), others report contradictory results (e.g., Karbach et al, 2013;Silinskas & Kikas, 2019;Valle et al, 2016). Some scholars (Dinkelmann & Buff, 2016;Fan & Williams, 2010;Gonida & Cortina, 2014;Hoover-Dempsey et al, 2001;Karbach et al, 2013;Luo et al, 2016; argue these contradictions are because parental involvement in homework has a stronger association with children's psychological resources than with academic achievement.…”
Section: Types Of Parental Involvement With Homeworkmentioning
confidence: 99%
“…Studies adopting a bi-directional model of socialization (Belsky, 1984;Pastorelli et al, 2016) to analyze the reciprocal effects of parent-children relations in homework are relatively scarce. However, some scholars (Dumont et al, 2014;Luo et al, 2016;Núñez et al, 2017;Silinskas & Kikas, 2019;Valle et al, 2015) have reported that children's academic performance can be a behavioral driver leading parents to different types of involvement in homework. For example, previous studies show that children's low academic achievement is associated with more parental control in homework, whereas high achievement has lower parental control (Dumont et al, 2014;Núñez et al, 2017).…”
Section: The Role Of Children's Characteristics In Parental Involvemementioning
confidence: 99%
See 3 more Smart Citations